KIMERU-INFLUENCED MISSPELLINGS AND WRONG LEXICAL CHOICES IN THE KISWAHILI COMPOSITIONS OF THREE SCHOOLS IN MERU COUNTY, KENYA (The University of Nairobi Journal of Language and Linguistics, 2023)
The aim of this paper was to investigate the Kimeru-influenced misspellings and wrong lexical choices in the Kiswahili compositions of three schools in the Meru County of Kenya, with gender as a variable. The objectives were to establish which word categories were most involved in the said misspellings and wrong lexical choices and to establish whether gender was a determining factor in producing such language errors. A total sample of 90 students, selected through stratified random sampling from three schools (i.e. a sub-sample of 30 from each) was used. The 90 participants were required to write a composition. In relation to misspellings, the results show that quite a number of Kiswahili words were written the same way they would be pronounced in Kimeru, while in relation to the wrong lexical choices, verbs were the most borrowed category (at a rate 62%), with various other word categories sharing the remaining 38%. It also emerged that the male students made significantly more wrong lexical choices than the female ones (62% vs. 38).